THEORETICAL JUSTIFICATION OF THE PARAMETERS OF AN IMPROVED POTATO DIGGER - Karimov, Akmal (Innovatsion texnologiyalar, 2023)
This article presents an analysis of the work on the technique and equipment used for harvesting root crops. The purpose of the research is to improve the quality of potato digging and productivity by developing an improved potato digger. Research work is underway around the world aimed at improving energy- and resource-saving methods for digging up potatoes and the weapons that implement them. In particular, special attention is paid to the creation of energy- and resource-saving tools capable of high-quality and complete digging of potatoes in small areas. In this regard, it seems relevant to improve methods for digging potatoes, develop forced vibration potato diggers that implement them, and substantiate the technological process of their operation and the parameters of the working parts. The design diagram of an improved potato digger, the main parameters of lattice and intermediate shares and oscillating plows, the basics of the operating mode and the results of theoretical studies to determine traction resistance are presented. Based on the analysis of scientific and technical literature and patent information materials, a design diagram of an improved potato digger with a passive lattice plow and a vibrating hoe has been developed. It also provides detailed information about the proposed potato digger